K-means clustering for feature extraction from wavelet-based flute signals - Ang, Yew Yee (2010)
High Speed Machines (HSM) are machines that operate at cutting speeds significantly higher than those typically utilized for a particular material and are very important near-end-line manufacturing devices. The quality of cutting highly depends on cutter specifications, type of work piece and cutting conditions.